The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

An updated Irwin sensor for measurement of surface shear velocity - Nancy P. Ziegler; Nicholas P. Webb; Brandon L. Edwards; George Nikolich; John A. Gillies; Sahil G. Patel; Brandi Wheeler; Pei Zhang; Justin W. Van Zee; Sandra L. LeGrand; Andrew C. Trautz (Aeolian Research, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Evaluation of the WEPS hydrology sub-model for surface soil water content under different tillage practices in the inland Pacific Northwest, USA - Huawei Pi; David R. Huggins; Larry.E. Wagner; Fred. Fox; Sisi Li; Nicholas P. Webb (CATENA, 2025)

Crushing energy-based indicators of dry soil aggregate stability from contrastive land management practices in a semi-arid agroecosystem - Huawei Pi; Chuanzhou Wang; Sifeng Li; Sisi Li; Nicholas P. Webb (Ecological Engineering, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Dust transport pathways from The Great Basin - Ronald S. Treminio; Nicholas P. Webb; Saroj Dhital; Akasha Faist; Beth Newingham; Colby Brungard; David DuBois; Brandon L. Edwards; Emily Kachergis (Aeolian Research, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

An evaluation of different approaches for estimating shear velocity in aeolian research studies - Pei Zhang; Brandon L. Edwards; Nicholas P. Webb; Andrew Trautz; John A. Gillies; Nancy P. Ziegler; Justin W. Van Zee (Aeolian Research, 2024)

Characterizing variability in geochemistry and mineralogy of western US dust sources - Abby L. Mangum; Gregory T. Carling; Barry R. Bickmore; Nicholas Webb; DeTiare L. Leifi; Janice Brahney; Diego P. Fernandez; Kevin A. Rey; Stephen T. Nelson; Landon Burgener; Joshua J. LeMonte; Alyssa N. Thompson; et al. (Aeolian Research, 2024)

Influence of crop rotation, irrigation, fertilization, and tillage on the aggregate property and soil wind erosion potential in the floodplain of the Yellow River - Huawei Pi; Xiuli Zhang; Sisi Li; Nicholas P. Webb (Aeolian Research, 2024)

A new framework for evaluating dust emission model development using dichotomous satellite observations of dust emission - Mark Hennen; Adrian Chappell; Nicholas P. Webb; Kerstin Schepanski; Matthew C. Baddock; Frank D. Eckardt; Tarek Kandakji; Jeffrey A. Lee; Mohamad Nobakht; Johanna von Holdt (Science of The Total Environment, 2024)

Investigation on removal of perfluorooctanoic acid (PFOA), perfluorooctane sulfonate (PFOS), perfluorohexane sulfonate (PFHxS) using water treatment sludge and biochar - Minh Duc Nguyen; Anithadevi Kenday Sivaram; Mallavarapu Megharaj; Lawrence Webb; Sirjana Adhikari; Michael Thomas; Aravind Surapaneni; Ellen M. Moon; Nicholas A. Milne (Chemosphere, 2023)

Synergistic soil, land use, and climate influences on wind erosion on the Colorado Plateau: Implications for management - Travis W. Nauman; Seth M. Munson; Saroj Dhital; Nicholas P. Webb; Michael C. Duniway (Science of The Total Environment, 2023)

Managing an arid ranch in the 21st century: New technologies for novel ecosystems - Brandon T. Bestelmeyer; Santiago Utsumi; Sarah McCord; Dawn M. Browning; Laura M. Burkett; Emile Elias; Rick Estell; Jeffrey Herrick; Darren James; Sheri Spiegal; Nicholas P. Webb; Jebediah Williamson (Rangelands, 2023)

Satellites reveal Earth's seasonally shifting dust emission sources - Adrian Chappell; Nicholas P. Webb; Mark Hennen; Kerstin Schepanski; Philippe Ciais; Yves Balkanski; Charles S. Zender; Ina Tegen; Zhenzhong Zeng; Daniel Tong; Barry Baker; Marie Ekström; et al. (Science of The Total Environment, 2023)

Plant phenology drives seasonal changes in shear stress partitioning in a semi-arid rangeland - Nancy P. Ziegler; Nicholas P. Webb; John A. Gillies; Brandon L. Edwards; George Nikolich; Justin W. Van Zee; Brad F. Cooper; Dawn M. Browning; Ericha M. Courtright; Sandra L. LeGrand (Agricultural and Forest Meteorology, 2023)

Modelled direct causes of dust emission change (2001–2020) in southwestern USA and implications for management - Mark Hennen; Adrian Chappell; Nicholas P. Webb (Aeolian Research, 2023)

The effect of adolescent social isolation on vulnerability for methamphetamine addiction behaviours in female rats - Paige I. Webb; Timothy J. Hill; Nicholas A. Everett; Jade L. Thornton; Jennifer L. Cornish; Sarah J. Baracz (Psychopharmacology, 2022)
Rationale Stress exposure during adolescence contributes to developing a methamphetamine (METH) use disorder. However, most of the studies investigating addiction-related behaviours include only male rodents, despite METH addiction rates being higher in females. Furthermore, animal studies investigating the effects of stress on methamphetamine addiction have used only basic self-administration models which may not be sensitive to the effects of stress. Objectives This project explored whether adolescent isolation stress exposure increases the incidence of four key addiction-related behaviours in female rats. Methods Thirty-two female rat pups were caged in groups of four or individually during adolescence from postnatal (PND) day 22, with the latter being re-socialised in groups of four on PND 43. In adulthood, rats were tested for addiction-like behaviours in a METH self-administration paradigm modelling motivation to take METH, persistence in drug-seeking behaviour when METH was not available, resistance to extinction, and propensity to reinstate after a period of withdrawal. Results Adolescent social isolation resulted in lower METH intake during acquisition; however, the paradigm modelling drug-seeking when the drug was unavailable engendered intermittent METH bingeing in all rats, abolishing the group differences in intake during this phase. Adolescent social isolation also accelerated extinction of non-reinforced lever pressing, and increased stress-primed reinstatement, compared to the group-housed rats. Conclusions Adolescent social isolation stress alters various methamphetamine addiction-like behaviours in female rats.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Single-dose pharmacokinetics and safety of azilsartan medoxomil in children and adolescents with hypertension as compared to healthy adults - Nicholas J. A. Webb; Thomas Wells; Max Tsai; Zhen Zhao; Attila Juhasz; Caroline Dudkowski (European Journal of Clinical Pharmacology, 2016)

P alaeocene– E ocene evolution of beta diversity among ungulate mammals in N orth A merica - Simon A. F. Darroch; Amelinda E. Webb; Nicholas Longrich; Jonathan Belmaker (Global Ecology and Biogeography, 2014)
Aim The P alaeocene–late E ocene transition in N orth A merica marks a critical interval in the evolution and diversification of land mammals, including adaptive radiation in the P alaeocene, and repeated waves of immigration over habitat bridges at the P alaeocene– E ocene boundary. We investigate the fossil record of ungulate mammals over this period to understand the effects of immigration and faunal exchange on local (alpha), regional (gamma) and between‐site (beta) diversity. Location N orth A merica. Methods We use P alaeocene and E ocene records of N orth A merican ungulate mammals taken from the Paleobiology Database ( PBDB ), and calculate beta diversity among families and genera within the seven stages of the C enozoic. We reconstruct geographic ranges sizes for studied taxa, and test trends in these ranges against null models used to control for sampling biases. Finally, we use Mantel tests to quantify the relationship between geographic distance and faunal dissimilarity within each time slice, in order to visualize changes in the spatial complexity of mammal communities. Results Gamma diversity increases over the studied interval, with varying contributions from alpha and beta diversity. Beta diversity increases from the P alaeocene to E ocene, reflected in decreasing range size and increased correlation between reconstructed distance and faunal similarity. Increase in beta diversity over the P alaeocene– E ocene transition is driven by smaller geographic ranges among putatively invasive ‘immigrant’ and secondarily endemic taxa; range contraction among these groups in the middle–late E ocene leads to a B artonian peak in beta diversity. Main conclusions High gamma diversity in the E ocene was driven by high beta diversity rather than alpha diversity, indicating that range contraction in both immigrant and secondarily endemic taxa restructured the spatial organization of mammal communities. These parallel trends suggest that factors such as tectonic uplift or climate change were responsible, as opposed to ecological differences. Increase in beta diversity over the P alaeocene– E ocene boundary suggests that over longer time‐scales, mass immigration events can lead to greater overall richness and greater heterogeneity, rather than homogeneity, within regional assemblages.

Soil organic carbon dust emission: an omitted global source of atmospheric CO 2 - Adrian Chappell; Nicholas P. Webb; Harry J. Butler; Craig L. Strong; Grant H. McTainsh; John F. Leys; Raphael A. Viscarra Rossel (Global Change Biology, 2013)
Soil erosion redistributes soil organic carbon ( SOC ) within terrestrial ecosystems, to the atmosphere and oceans. Dust export is an essential component of the carbon (C) and carbon dioxide ( CO 2 ) budget because wind erosion contributes to the C cycle by removing selectively SOC from vast areas and transporting C dust quickly offshore; augmenting the net loss of C from terrestrial systems. However, the contribution of wind erosion to rates of C release and sequestration is poorly understood. Here, we describe how SOC dust emission is omitted from national C accounting, is an underestimated source of CO 2 and may accelerate SOC decomposition. Similarly, long dust residence times in the unshielded atmospheric environment may considerably increase CO 2 emission. We developed a first approximation to SOC enrichment for a well‐established dust emission model and quantified SOC dust emission for Australia (5.83 Tg CO 2 ‐e yr −1 ) and Australian agricultural soils (0.4 Tg CO 2 ‐e yr −1 ). These amount to underestimates for CO 2 emissions of ≈10% from combined C pools in Australia (year = 2000), ≈5% from Australian Rangelands and ≈3% of Australian Agricultural Soils by Kyoto Accounting. Northern hemisphere countries with greater dust emission than Australia are also likely to have much larger SOC dust emission. Therefore, omission of SOC dust emission likely represents a considerable underestimate from those nations’ C accounts. We suggest that the omission of SOC dust emission from C cycling and C accounting is a significant global source of uncertainty. Tracing the fate of wind‐eroded SOC in the dust cycle is therefore essential to quantify the release of CO 2 from SOC dust to the atmosphere and the contribution of SOC deposition to downwind C sinks.

The significance of carbon‐enriched dust for global carbon accounting - Nicholas P. Webb; Adrian Chappell; Craig L. Strong; Samuel K. Marx; Grant H. McTainsh (Global Change Biology, 2012)
Soil carbon stores amount to 54% of the terrestrial carbon pool and twice the atmospheric carbon pool, but soil organic carbon ( SOC ) can be transient. There is an ongoing debate about whether soils are a net source or sink of carbon, and understanding the role of aeolian processes in SOC erosion, transport and deposition is rudimentary. The impacts of SOC erosion by wind on the global carbon budget, and its importance for carbon accounting remain largely unknown. Current understanding of SOC losses to wind erosion is based on the assumption that the SOC content of eroded material is the same as that of the parent soils. However, measured enrichment factors for the SOC content of A ustralian dusts relative to parent soils show that the SOC content of dusts can be up to seven times (by weight) larger than that of source‐area soils, with enrichment factors ranging from 1.67 to 7.09. Assuming dust emissions from the continent of ~110 Mt yr −1 , SOC dust emissions would be 0.13–4.65 Mt SOC yr −1 without enrichment but 0.94–7.77 Mt SOC yr −1 with enrichment; which represents an uncertainty of around 60%. Representing SOC enrichment within dust emission models will reduce uncertainty in estimates of the impact of wind erosion on SOC flux and provide an approach for the inclusion of wind erosion processes in carbon accounting systems.

Interacting effects of vegetation, soils and management on the sensitivity of Australian savanna rangelands to climate change - Nicholas P. Webb; Chris J. Stokes; Joe C. Scanlan (Climatic Change, 2012)

Patterns and causes of species richness: a general simulation model for macroecology - Nicholas J. Gotelli; Marti J. Anderson; Hector T. Arita; Anne Chao; Robert K. Colwell; Sean R. Connolly; David J. Currie; Robert R. Dunn; Gary R. Graves; Jessica L. Green; John‐Arvid Grytnes; Yi‐Huei Jiang; et al. (Ecology Letters, 2009)
Understanding the causes of spatial variation in species richness is a major research focus of biogeography and macroecology. Gridded environmental data and species richness maps have been used in increasingly sophisticated curve‐fitting analyses, but these methods have not brought us much closer to a mechanistic understanding of the patterns. During the past two decades, macroecologists have successfully addressed technical problems posed by spatial autocorrelation, intercorrelation of predictor variables and non‐linearity. However, curve‐fitting approaches are problematic because most theoretical models in macroecology do not make quantitative predictions, and they do not incorporate interactions among multiple forces. As an alternative, we propose a mechanistic modelling approach. We describe computer simulation models of the stochastic origin, spread, and extinction of species’ geographical ranges in an environmentally heterogeneous, gridded domain and describe progress to date regarding their implementation. The output from such a general simulation model (GSM) would, at a minimum, consist of the simulated distribution of species ranges on a map, yielding the predicted number of species in each grid cell of the domain. In contrast to curve‐fitting analysis, simulation modelling explicitly incorporates the processes believed to be affecting the geographical ranges of species and generates a number of quantitative predictions that can be compared to empirical patterns. We describe three of the ‘control knobs’ for a GSM that specify simple rules for dispersal, evolutionary origins and environmental gradients. Binary combinations of different knob settings correspond to eight distinct simulation models, five of which are already represented in the literature of macroecology. The output from such a GSM will include the predicted species richness per grid cell, the range size frequency distribution, the simulated phylogeny and simulated geographical ranges of the component species, all of which can be compared to empirical patterns. Challenges to the development of the GSM include the measurement of goodness of fit (GOF) between observed data and model predictions, as well as the estimation, optimization and interpretation of the model parameters. The simulation approach offers new insights into the origin and maintenance of species richness patterns, and may provide a common framework for investigating the effects of contemporary climate, evolutionary history and geometric constraints on global biodiversity gradients. With further development, the GSM has the potential to provide a conceptual bridge between macroecology and historical biogeography.

Carbonate alteration of the Upper Mount McRae Shale beneath the martite-microplaty hematite ore deposit at Mount Whaleback, Western Australia - Adam D. Webb; Gerald R. Dickens; Nicholas H. S. Oliver (Mineralium Deposita, 2004)